Penerapan Metode Pembelajaran Problem Based Learning (Pbl) untuk Meningkatkan Hasil Belajar Siswa Pada Materi Pendidikan Agama Islam Kelas X di SMAN 1 Setu - Mulyadi, Acep; Fatmala, Siti; Tsumu, Damara Mumtaz; Yulianti, Diva; Islami, Tasya Bilkis (LPPM Institut Pendidikan Nusantara Global, 2024)
This research is intended to enhance the achievement of Islamic Religious Education (PAI) learning outcomes for the students of class X.C at SMA Negeri 1 Setu by applying the cooperative learning method, specifically the Problem-Based Learning (PBL) model. The study involved 34 students as subjects, and data collection methods included observation, tests, and documentation. The research was conducted in three cycles to observe the impact of the learning method implementation. The results of the research indicate that the application of the PBL learning model successfully improved PAI learning outcomes for class X.C students at SMAN 1 Setu. In the initial test before the first cycle of pre-action, 11 students (32%) successfully achieved the minimum passing grade (KKM) of 75, with an average score of 69.38. After the first cycle, 27 students (79%) achieved an average score of 85.03 and could reach the KKM, although the score of 75 was not yet fully achieved. Therefore, the researcher proceeded to cycle 2. In cycle 2, students' learning outcomes continued to improve, with 29 students (85%) achieving an average score of 89.94. In cycle 3, all students, a total of 34 individuals or 100%, successfully reached the minimum standard score with an average score of 92.21. From these findings, it can be concluded that the PBL learning model significantly improved PAI learning outcomes for class X.C students at SMAN 1 Setu. The implementation of this model can serve as a reference for enhancing the effectiveness of learning in the future.